Answer:
The discriminant is 0
Step-by-step explanation:
In a quadratic equation , we use the quadratic formula to find the solutions
x = (-b ± √(b2 - 4ac)) / 2a
where a, b, and c are coefficients of the equation
ax2 + bx + c = 0
Since x=6 is the only x-intercept, the equation would be
(x - 6)(x - 6) = 0
Expanding this out, we get
x2 - 12x + 36 = 0
In this equation,
a = 1
b = -12
c = 36
Now the discriminant is the square-root part of the formula:
b2 - 4ac
Now plug in the values of a,b, and c into the discriminant.
(-12)2 - 4(1)(36) = 144 - 144 = 0
This number is under the square-root. The square-root of 0 is 0.